PHYSICAL CULTURE AS A MOTOR FACTOR OF MENTAL PERFORMANCE OF ADOLESCENTS - Muydinov Ikboljon Abdukhamidovich; Sarukhanov Arsen Albertovich; Azizov Mukhammadjon Azamovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
There is a close connection between the mental and physical development of a person, which is fully clarified when studying the human body and its functions. Mental growth and development require appropriate development of physical education.